Sodium–glucose co-transporter-2 inhibitors - empagliflozin and dapagliflozin as future therapy for Alport Syndrome, literature review - Kłusek, Magdalena; Chawrylak, Katarzyna; Kuszneruk, Julia; Kubas, Maria; Krzemińska, Katarzyna (Quality in Sport, 2024)
Introduction and purposes: Alport syndrome (AS) is a common hereditary kidney disorder for which there is currently no curative treatment. The current standard of care for AS involves therapeutic blockade of the renin-angiotensin-aldosterone system (RAAS). This review explores the potential of sodium-glucose co-transporter-2 (SGLT2) inhibitors (SGLT2i) as a treatment option that may slow the progression of chronic kidney disease (CKD) and prevent the advancement to end-stage kidney disease (ESKD). Materials and Methods: A systematic literature search was conducted using PubMed and Google Scholar, employing the following search terms: 'Alport syndrome,' 'SGLT2' 'inhibitors,' ‘sodium-glucose transporter 2 inhibitors’, 'proteinuria,' 'albuminuria,' 'empagliflozin,' 'dapagliflozin.' Articles published between 2019 and 2024 were included in the search. Results: Recent randomized clinical trials have shown that SGLT2i have nephroprotective effects in CKD. SGLT2i may effectively address the hemodynamic overload in addition to RAAS-blockade in AS patients, potentially delaying end-stage renal failure (ESRF) by several years. Studies indicate that empagliflozin and dapagliflozin are well tolerated and significantly reduce proteinuria in patients with AS. However, they may also cause an initial decrease in estimated glomerular filtration rate (eGFR), raising some safety concerns. This highlights the importance of monitoring and evaluating the treatment course in every AS patient starting SGLT2i therapy. Conclusion: Our findings contribute to the growing evidence that SGLT2i reduce proteinuria and may slow disease progression. They could become a future standard of care for patients with glomerular kidney diseases like AS. Future research should investigate the earlier use of SGLT2i in treatment and monitor long-term outcomes in treated patients.